Modelling of intracellular calcium dynamics - Tilūnaitė, Agnė (2018)
Ca2+ as a universal messenger participates in a great variety of physiological functions and biological events such as cell maturation, chemotaxis or gene expression. These diverse functions are controlled through complex spatio-temporal calcium patterns. To date it is known that these patterns depend on stimuli type and concentration. However, the majority of these observations were from constant or step change stimulation protocols. Under these conditions two leading hypotheses for the stimulus encoding into cytosolic calcium responses were proposed, namely amplitude and frequency modulation.